Analysis of Market Structure, Conduct, and Performance of the Lemuru Fish in Muncar District, Banyuwangi Regency, East Java - Aditya Bagus Wicaksana; Budi Setiawan; Abdul W. Muhaimin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
In general, the marketing of fishery products is potentially inefficient. This study aims to analyze the structure, conduct, and performance of the Lemuru fish market in Muncar District, Banyuwangi Regency. The method used to analyze the data obtained at the research site is descriptive qualitative quantitative. The results showed that the structure of the Lemuru fish market formed a tight oligopoly market and concentrated on fish collectors. The CR4 value is 90% for collectors, 30% for retailers, and 18% for fishers. The shape of the market structure affects market conduct where traders are in the price-makers position while fishers are price-takers. The form of vertical business integration in the Lemuru fish market is a cooperation between collectors and retailers to increase profits and dominate the market. The causal relationship between market structure and market conduct forms an efficient market performance with share values in both marketing channels exceeding the standard efficiency values set at 47.37% in channel I and 52.94% in channel II. The results of this study indicate the importance of the role of local governments in carrying out fish auctions according to their functions, providing counseling on fishery capital loan programs, and processing added value to fishers. In addition, this research is also helpful for fishers related to loans for fishing businesses, prices, market needs, and added value of Lemuru fish.